Clinical Use of Anti-Xa Monitoring in Malignancy-Associated Thrombosis. (12th October 2015) - Yentz, Sarah; Onwuemene, Oluwatoyosi A.; Stein, Brady L.; Cull, Elizabeth H.; McMahon, Brandon
Abstract : Introduction . Low molecular weight heparin (LMWH) is preferred for malignancy-associated venous thromboembolism (VTE). Many providers monitor LMWH with anti-Xa levels, despite little validation on correspondence with patient outcome. Methods . This is a retrospective, single institution study of anti-Xa measurement in malignancy-associated thrombosis. Cases were identified using the Electronic Data Warehouse, and inclusion was confirmed by two independent reviewers. Malignancy type, thrombotic history, measurement rationale and accuracy, clinical context, and management changes were evaluated. Results . 167 cases met inclusion criteria. There was no clear rationale for anti-Xa testing in 56%. Impaired renal function (10%), documented or suspected recurrent thrombosis despite anticoagulation (9%), and bleeding (6%) were the most common reasons for testing. Incorrect measurement occurred in 44%. Renal impairment was not a significant impetus for testing, as 70% had a GFR > 60. BMI > 30 was present in 40%, and 28% had a BMI < 25. Clinical impact was low, as only 11% of patients had management changes. Conclusions . Provider education in accuracy and rationale for anti-Xa testing is needed. Our study illustrates uncertainty of interpretation and clinical impact of routine anti-Xa testing, as management was affected in few patients. It is not yet clear in which clinical context providers should send anti-Xa levels.